2023
DOI: 10.1167/iovs.64.2.15
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Alternate Flicker Modulates Binocular Interaction in Adults With Abnormal Binocular Vision

Abstract: Purpose The current understanding of binocular processing is primarily derived from static spatial visual perception: this leaves the role of temporal information unclear. In this study, we addressed this gap by testing the effect of alternating flicker on binocular information processing in adults with abnormal binocular vision. Our goal was to determine which temporal frequency optimally balanced input from both eyes. Methods We took measurements in four groups of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Previous research on flicker stimuli 25 indicated that flickering could alter luminance transmission, leading to a decrease in the average luminance in front of the flickered eye. Although luminance reduction in one eye could lessen its contribution in binocular integration, 35 37 could the flickering-induced luminance transmission alternation explain the temporal frequency dependency pattern found in the current study?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on flicker stimuli 25 indicated that flickering could alter luminance transmission, leading to a decrease in the average luminance in front of the flickered eye. Although luminance reduction in one eye could lessen its contribution in binocular integration, 35 37 could the flickering-induced luminance transmission alternation explain the temporal frequency dependency pattern found in the current study?…”
Section: Discussionmentioning
confidence: 99%
“…First, for instance, Schor et al 24 demonstrated that alternately presenting targets to the two eyes at 2 and 7 Hz in amblyopia potentially enables better visual acuity under binocular viewing compared with other temporal frequencies. Next, our preliminary research 25 indicated that binocular alternating flicker at 7 Hz (where flicker stimuli are presented alternately in front of each eye with a 1:1 ratio of light to dark through liquid crystal spectacles) enables better binocular balance in amblyopia. Modulation of binocular imbalance via flicker can also reveal further insights regarding the neural underpinnings of amblyopia: several studies using synchronous binocular flicker (where stimuli are flickered simultaneously in front of both eyes) have observed a slightly larger interocular imbalance at low temporal frequencies in amblyopia.…”
mentioning
confidence: 99%
“…In contrast, semiactive suspensions are less costly and have an adjustable damping force. By applying control algorithms to semiactive suspensions, they can be adaptively adjusted according to the current and future road conditions, which is a better choice for suspension systems currently [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%